Surgery for Gastroenteropancreatic Neuroendocrine Tumor Liver Metastases - Etherington, Mark S.; Roses, Robert E. (Digestive Disease Interventions, 2019)
Gastroenteropancreatic-neuroendocrine tumors (GEP-NETs) arise from endocrine cell types along the luminal gastrointestinal tract and pancreas. Stage and grade are dominant predictors of outcome. Optimal management of localized, lower-grade GEP-NETs involves surgical resection, which is associated with excellent long-term survival. While high-grade disease is almost always associated with rapid disseminated progression, metastatic, well-differentiated GEP-NETs can progress slowly and are compatible with prolonged survival. Management of patients with an advanced spectrum of lower grade disease can include a range of systemic and local therapies and requires multidisciplinary collaboration. While controversy persists regarding the optimal scope and sequencing of therapy, surgical management can have a substantial impact alone or in combination with other therapies.
Keywords: neuroendocrine tumor; liver metastases; metastasectomy